Kulturne kompetence medicinskih sester in babic - Loredan, Irena (Obzornik zdravstvene nege, 2013)
In the times of global migration, it is of utmost importance that nurses and midwives possess adequate knowledge of different cultures that enables them to provide effective and culturally competent nursing and midwifery care. Nurses and midwives must recognize cultural differences, values and their importance for the patient, their family or wider community. These observations present grounds for decision making and preservation of cultural integrity during nursing and midwifery care delivery. Cultural competence is defined as a process to achieve the ability to interact effectively with people of different cultures in accordance with the cultural context and background of a client. The model of Campinha-Bacote cultural competence is the most widely used model of cultural competence in everyday health care delivery. This model is defined as a dynamic ongoing process which involves the integration of cultural awareness, cultural knowledge, cultural skill, cultural encounters and cultural desire which are the five constructs of cultural competence. Cultural competence represents an integral element in the elimination of disparities in health care.
Keywords: babiška nega; cultural competences; culture; disparities in health care; kultura; kulturne kompetence; medicinske sestre; midwifery; nursing; zdravstvena nega